STRATEGI KOMUNIKASI PEMASARAN BALI FOOD SAFARI DALAM MENINGKATKAN AWARENESS KONSUMEN - Murfiyaningrum, Arita Nurul; Purnawan, Ni Luh Ramaswati; Pascarani, Ni Nyoman Dewi (E-Jurnal Medium, 2018)
ABSTRACT Bali Food Safari (BFS) is a culinary tour in Bali which was established in November 2013 with a unique mystery culinary dinner tour concept. This research have a purpose to describe the intergrated marketing communication strategic of BFS for increasing consumer awareness based on Intergrated Marketing Communication (IMC) theory with descriptive-qualitative approach. The result of this research is showed that BFS using six channel from IMC, which is advertising, direct marketing, sales promotion, interactive marketing, personal selling, and word of mouth. And one channel that not used by Bali Food Safari yet is public relations. Bali Food Safari marketing communication activities is pointed on online media which is advertising and promotion by Facebook and Instagram. But the consistency of message delivery in channels that used is not consistent yet, this is indicated by lack of use the mystery word which is the keyword of mystery culinary dinner tour. Keywords : Intergrated Marketing Communication Strategy, Awareness, Mystery Culinary Dinner Tour, Bali Food Safari.